Tingkat Pengetahuan, Beban Kerja, Pengawasan, dan Penerapan SOP dengan Kejadian Kecelakaan Kerja di PT X - Mila Amelia Putri; Ahmad Irfandi; Namira Wadjir Sagadji; Mayumi Nitami (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
There were 19 instances of working accidents in 2023, according to PT X's data on workplace incidents. The results of the root cause analysis showed that a lack of understanding of workplace safety, heavy workloads, insufficient supervision, and a failure to follow safety operating procedures (SOPs) were the main causes of workplace accidents. The aim of this research is to ascertain the correlation between PT X employees' knowledge levels, workloads, supervision, and SOP implementation and workplace accidents. Analytical survey research using a cross-sectional study methodology is what this study is. There are 449 production workers in the electrical guitar sector, making up the study's population. Based on the Lemeshow approach, a sample size of 77 workers was determined. A basic random sampling methodology is combined with probability sampling as the sampling method. Chi-square tests and prevalence ratios were used to examine the data. The findings indicate a correlation between workload and workplace accidents (p-value 0.006 < 0.05), knowledge level and workplace accidents (p-value 0.001 < 0.05), workplace accidents and supervision (p-value 0.007 < 0.05), and workplace accidents and the application of SOPs (p-value 0.001 < 0.05). It is possible to draw conclusions from these findings regarding the correlation between PT X employees' knowledge levels, workloads, supervision, and SOP implementation and workplace accidents.